Hubungan kecanduan online game dengan kecemasan pada remaja pengunjung game centre di Kelurahan Jebres Surakarta - Putri, Asri Sukawati; Suwito, Djoko; Dharmawan, Ruben (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background : Perfection graphics technologies in online gaming becomes allure for players, especially for adolescents. Some previous studies have claimed that online gaming addiction can affect the physical and psychological players, one of which may cause anxiety. This study aims to prove the relationship between addiction to online games with anxiety. Methods: This is a descriptive analysis research with a cross sectional approach. Subjects were adolescents game centre visitor in the Jebres Village . The samples are adolescents of the age 12-21 years old. Samples were taken purposively sampling. Data collection techniques using the TMAS anxiety scale, the scale of online gaming addiction questionnaires and Family Intimacy Instrument. Data scores online gaming addiction, anxiety and family intimacy were analyzed with multiple logistic regression analysis model. Result : This research obtained 35 young males. The results of multiple logistic regression analysis showed that there is a positive relationship between online game addiction and anxiety in adolescents in the Village Jebres. Adolescents with online gaming addiction have a risk 2.86 times greater for anxiety than adolescents without online gaming addiction p = 0.212. (OR: 2.86 CI 95% 0.55 s / d 14.91). The results of this analysis also showed an association between family intimacy and anxiety. Adolescents with low family intimacy had 0.51 times the risk for anxiety with p = 0.440 (OR = 0.51). However, online gaming addiction pose a greater risk of experience anxiety than the risks posed by families with low intimacy. Conclusion : There is relationship between online game addiction and anxiety. The higher the level of adolescent addiction to online games, the higher the risk for anxiety. Keywords : adolescent, online game addiction, anxiety, family intimacy